Penggunaan Media Spinning Wheel Dalam Pembelajaran Qawaid Nahwu - Nisa Fahmi Huda (Universitas Yudharta Pasuruan, 2020)
It feels familiar to us with one of the Arabic subjects. Moreover, Arabic learning has existed at the school level from elementary to tertiary education. Arabic learning must stand and cannot be separated from several kinds of language skills, such as listening, speaking, reading, and writing. However, apart from the four language skills, we must pay attention to one of the important aspects of language and this is also not separated because without this aspect, language will not be organized. These important aspects are the nahwu rules that we must learn and cannot be separated from the four skills of Arabic. The purpose of this study was to determine how effective the use of the spinning wheel media was in learning Arabic, especially in the subject of qawaid nahwu. Data collection methods used observation, interviews, tests, and documentation. The approach used is quantitative with the type of research Quasi Experimental One Group Pretest Posttest. The result of this research is that the use of the spnning wheel media can improve the qawaid nahwu learning process in the seventh grade training of the students of the Darul Qur'an Wal Islamic Boarding School, Wonosari, Gunungkidul, Yogyakarta.